Pediatric sleep electrophysiology: Using polysomnography in developmental cognitive neuroscience - Lena M. Gaudette; Allison M. Swift; Melissa N. Horger; Jennifer F. Holmes; Rebecca M.C. Spencer (Developmental Cognitive Neuroscience)
Research suggests a bidirectional relationship between brain and cognitive development and sleep in early childhood. Polysomnography is essential for the investigation of the mechanisms underlying sleep’s role in brain and cognitive development. This paper outlines methods for integrating measures of sleep and sleep physiology into cognitive developmental neuroscience research. There are various options when choosing a polysomnography system depending on the research question. We offer considerations such as application time, recording time, montage density and analysis options, and cost. We also review suggestions for modifying procedures with developmental populations to support high quality polysomnography data collection. We hope that this overview will facilitate more developmental cognitive neuroscience studies of sleep to advance our understanding of early brain and cognitive development.